Diophantine triplet

The number of triplets of positive integers ( x , y , z ) (x, y, z) such that 2 x + 1 = 7 y + 2 z 2^x+1=7^y+2^z is

1 4 2 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hongqi Wang
Dec 4, 2020

2 x + 1 = 7 y + 2 z 2 x 2 z = 7 y 1 2 z ( 2 x z 1 ) = ( 7 1 ) i = 0 y 1 7 i 2 z ( 2 x z 1 ) = 2 3 i = 0 y 1 7 i 2 z ( 2 x z 1 ) = 2 ( 2 2 1 ) i = 0 y 1 7 i 2^x + 1 = 7^y + 2^z \\ 2^x - 2^z = 7^y - 1 \\ 2^z \cdot (2^{x-z} - 1) = (7 - 1) \cdot \sum\limits_{i=0}^{y-1} 7^i \\ 2^z \cdot (2^{x-z} - 1) = 2 \cdot 3 \cdot \sum\limits_{i=0}^{y-1} 7^i \\ 2^z \cdot (2^{x-z} - 1) = 2 \cdot (2^2 - 1) \cdot \sum\limits_{i=0}^{y-1} 7^i \\ As there is factor 3 at right side, so x z x-z must be even. Let x z = 2 k x-z = 2k , then 2 z ( 2 x z 1 ) = 2 z ( 4 k 1 ) = 2 z ( 2 2 1 ) i = 0 k 1 4 i 2 z 1 i = 0 k 1 4 i = i = 0 y 1 7 i \\ 2^z \cdot (2^{x-z} - 1) = 2^z \cdot (4^k - 1) \\ = 2^z \cdot (2^2 - 1) \cdot \sum\limits_{i=0}^{k-1} 4^i \\ \\ \therefore 2^{z-1} \cdot \sum\limits_{i=0}^{k-1} 4^i = \sum\limits_{i=0}^{y-1} 7^i \\

  • if y = 1 y = 1 , then z = 1 , x = 3 z= 1, x = 3

  • if y = 2 y = 2 , then z = 4 , x = 6 z= 4, x = 6

  • any else?

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...